A New Process of Capturing Carbon Dioxide Gas From The Atmosphere Using Solid & Aqueous Sorbents in Pilot Plant - Akash Talapatra (Program Pascasarjana Universitas Sriwijaya, 2019)
The capturing process of CO2 directly from air has been developed largely considering with commercial scale in pilot plants. This is done so that the capture CO2 from air can be used as a feedstock or raw material for producing carbon free renewable fuels by applying direct air capture (DAC) process. This way of capturing is gone to be possible with using some solid & aqueous sorbents in pilot plant. The success of this capturing process is depended on the appropriate configurations of both major & minor plant operations. Heat & mass balance are required necessarily to contribute on the finding of each pilot plants data. The design of this process is modeled like this so that the captured CO2 can be delivered at 15MPa into the pilot plant & for this, the requirements of energy inputs are about 8.81GJ or 5.25GJ of natural gas & 0 KWHr or 336KWHr of electricity respectively. Then all the results finding from the pilot contactor, reactor, calciner are optimized to reduce the processing cost of the capturing process. It is observed after the ending of the process that the amount of operating cost is ranged between 50 to 100 to capture per ton of CO2 from surrounding air where the total levelized cost of the whole process ranges between 94 to 232/t-CO2. If it considers the other specific choices such as financial safety, environ mental & ecological arrangements etc. then this DAC process would be the best reliable solution to capture the CO2 from air in upcoming decades.